2007
DOI: 10.3174/ajnr.a0687
|View full text |Cite
|
Sign up to set email alerts
|

Lobar Distribution of Changes in Gray Matter and White Matter in Memory Clinic Patients: Detected Using Magnetization Transfer Imaging

Abstract: BACKGROUND AND PURPOSE:Previous studies have shown involvement of both gray matter (GM) and white matter (WM) in mild cognitive impairment (MCI) and Alzheimer disease (AD). In this study, we assessed the lobar distribution of the GM and WM pathology over the brain and the association of lobar distribution with global cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…In all previous MT imaging studies in AD and MCI, no side evaluation of lobar or regional MT ratio was reported, and data related to the 2 sides were typically averaged. [9][10][11][12]14,18 In our study, the voxelwise analysis did not show any region exhibiting significantly different MT ratio in the group of patients with amnestic MCI with respect to healthy control subjects, and automatic VOI analysis of the hippocampus and amygdala in the patients with amnestic MCI showed values for the MT ratio that were between the values computed for healthy control subjects and patients with AD. This result is in line with the results obtained with manual segmentation of the anterior hippocampus in a prior study, 14 whereas it represents a partial discrepancy with prior investigations in which the MT ratio of the whole brain or temporal lobe was found to be significantly decreased in patients with MCI as compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In all previous MT imaging studies in AD and MCI, no side evaluation of lobar or regional MT ratio was reported, and data related to the 2 sides were typically averaged. [9][10][11][12]14,18 In our study, the voxelwise analysis did not show any region exhibiting significantly different MT ratio in the group of patients with amnestic MCI with respect to healthy control subjects, and automatic VOI analysis of the hippocampus and amygdala in the patients with amnestic MCI showed values for the MT ratio that were between the values computed for healthy control subjects and patients with AD. This result is in line with the results obtained with manual segmentation of the anterior hippocampus in a prior study, 14 whereas it represents a partial discrepancy with prior investigations in which the MT ratio of the whole brain or temporal lobe was found to be significantly decreased in patients with MCI as compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 72%
“…[14][15][16] In its simplest version, MT is obtained with acquisition of a pair of images without and with a specific radiofrequency offresonance prepulse followed by image subtraction and computation of the MT ratio. MT ratio is decreased in the temporal lobe and hippocampus of patients with AD independent from atrophy [9][10][11][12]14,17,18 ; is variably correlated with clinical severity, neuropsychological measurements, and disease duration [9][10][11][12] ; and appears capable to track progression of regional GM microstructural changes in AD. 18 MT ratio was also reported to be decreased in the whole brain, whole temporal lobe, or temporal lobe GM and WM in patients with amnestic MCI as compared with agematched healthy control subjects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports demonstrated an association between histogram parameters and cognition, 15,19 whereas others have not. 17,33 The histogram parameters analyzed here also did not show any association with cognition. One possible explanation is that we performed our analyses on a relatively small cohort of patients with mild to moderate AD, while van Flier et al 15 performed an analysis across different groups of dementia severity, including subjects with mild cognitive impairment and thus a much larger range of cognitive performance.…”
Section: Discussionmentioning
confidence: 87%